Investigating Students’ Academic Self-Efficacy in Play Performance Class - Mukti, Thomas Wahyu Prabowo; Triprihatmini, Veronica (SALEE: Study of Applied Linguistics and English Education, 2025)
Play Performance class at the English Language Education Study Program of Sanata Dharma University is designed to introduce students to fundamental concepts of drama and elaborate underlying principles of drama performance that come into play. In this course, not only do students learn about drama aspects, but they are also actively encouraged to practice and perform their soft skills in dealing with various challenges in preparing the performances. The researchers focused on finding out students’ academic self-efficacy in dealing with diverse challenges in this class. The researchers analyzed 29 students’ progress test 1, progress test 2, and final test reflection to investigate the students’ academic self-efficacy developments and factors contributing to the academic self-efficacy. The results showed that most students considered themselves not having self-efficacy at the beginning of the class. However, after facing several challenges, students’ academic self-efficacy was growing. This study illuminates the positive impact of giving students challenges to foster self-efficacy while practicing their English skills. The findings imply that educators should provide students enough opportunities to grow from both successes and failures in the context of academic journey and provide adequate supports during the period.